Enterococcus faecalis and Staphylococcus aureus stimulate nitric oxide production in macrophages and fibroblasts in vitro - Sousa, Mauricio Gonçalves da Costa (2020)
Aim: Nitric oxide (NO) is an important mediator related to damage of the pulp tissue and at the same time to regenerative pulp processes. However, it is not clear how common endodontic microorganisms can regulate this mediator. This study aimed to investigate NO production by macrophages and fibroblasts against Enterococcus faecalis- and Staphylococcus aureus-antigens. Methods: RAW 264.7 macrophages and L929 fibroblast cell lines were stimulated with different heat-killed (HK) antigen concentrations (105-108 colony forming units - CFU) from E. faecalis and S. aureus with or without interferon-gamma (IFN-γ). Cell viability by MTT colorimetric assay and NO production from the culture supernatants were evaluated after 72 h. Results: Data here reported demonstrated that none of the antigen concentrations decreased cell viability in macrophages and fibroblasts. The presence of HK-S. aureus and HK-E. faecalis antigen- stimulated NO production with or without IFN-γ on RAW 264.7. The HK-S. aureus antigen stimulated NO production in L929 fibroblasts with or without IFN-γ, and the highest concentration of HK-E. faecalis with IFN-γ also stimulated NO production by these cells. Conclusion: The amount of NO produced by macrophages and fibroblasts may be involved in the concentration and type of prevalent endodontic microorganisms, generating new answers for the understanding of pulpal revascularization/regeneration processes.